2007
DOI: 10.3136/fstr.13.45
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Intestinal Absorption of Soy Protein By Enzymatic Digestion to Oligopeptide in Healthy Adult Men

Abstract: In this study, we compared the intestinal absorption from di#erent sources with the same amino acid composition (protein, peptide, and amino acid mixture) by measuring changes in serum concentrations of various amino acids. Peptides used in this study were prepared by enzymatic digestion of ++S globulin (a major component of soy protein). Twelve normal male adults were asked to drink beverages containing +,./ g of the test sample, representing /ῌ suspension of each of the following three di#erent preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Clemente (2000) also found that protein hydrolysates were better absorbed than whole proteins. Their works and others (Maebuchi et al, 2007) showed that the peptide transport system plays a major role in the absorption of protein and peptide digestive products.…”
Section: The Amino Acids Of Gi Digestsmentioning
confidence: 98%
“…Clemente (2000) also found that protein hydrolysates were better absorbed than whole proteins. Their works and others (Maebuchi et al, 2007) showed that the peptide transport system plays a major role in the absorption of protein and peptide digestive products.…”
Section: The Amino Acids Of Gi Digestsmentioning
confidence: 98%
“…The results obtained indicated that two-step enzymatic hydrolysis followed by multistage separation was effective in producing short oligopeptides and in removing large peptides or undigested proteins. It was reported that oligopeptide mixtures prepared from proteins had improved absorption properties, high solubility, low viscosity, and low allergenicity associated with low molecular weight peptides (Maebuchi et al, 2007). Moreover, small activity peptides are better candidates than longer peptides to play a physiological role in vivo as they are less susceptible to undergo gastrointestinal hydrolysis (Gómez-Ruiz, Ramos, & Recio, 2007).…”
Section: Molecular Weight Distribution Of Sscpmentioning
confidence: 98%
“…At this stage, more than 60% of the amino acids were present as peptides. It has been reported that some small molecular-sized peptides are directly absorbed through the intestine by a peptide transport system which plays an important role in the digestion and the absorption of protein [31].…”
Section: Effect Of In Vitro Digestion On Amino Acid Contents Of Jhpmentioning
confidence: 99%